Nanotechnological development of us military capabilities in 21 st century - Korać, Srđan (Vojno delo, 2024)
The paper examines publicly available scientific achievements and technical and technological innovations in nanotechnology brought into the context of the modernization of US military capabilities. The starting assumption is that the development of sophisticated military capabilities centred around achievements of the Fourth Industrial Revolution is a key guarantor of sustainable military power in 21 st century, or successful global projection of armed force as a means of preserving hegemony worldwide. The analysis focuses on achieved and anticipated breakthroughs with the potential for military application resulting from publicly available primary and applied scientific and developmental projects in the field of nanotechnologies covered by the defence budget, as well as on achievements presented in scientific and professional literature. The analysis includes achievements in the following fields: advanced materials, explosives and their detectors, nano drones and nanorobots, microsatellites, and cyborg soldiers. The author concludes that the future utilization of the breakthroughs in the development of nanotechnology for military purposes can be limited by problems of the functional integration of sophisticated solutions into the military-strategic, operational and tactical framework, hence, the technological "leap" does not necessarily lead to greater effectiveness of military capabilities on the battlefield.